Routine hematology description and D-dimer COVID-19 patients at Sidoarjo Regional Hospital - Nugroho Eko Wirawan Budianto; Budhi Setiawan; Nugrahadi Dwi Pasca Budiono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: COVID-19, caused by the SARS-COV-2 virus, is a contagious and potentially fatal disease that is commonly diagnosed using real-time reverse polymerase chain reaction (RT-PCR) assay. Studies have shown that the D-dimer level and the features of hematological exams can offer important prognostic value of the patients. This study aimed to describe data about the routine hematology features and D-Dimer levels of hospitalized COVID-19 patients in Sidoarjo Regional Hospital. Methods: This study used a retrospective, cross sectional, observational approach with descriptive analysis. Medical records of 167 COVID-19 patient were collected based on the criteria. The outcomes of the D-dimer and complete blood count of the patients were summarized. Results: According to the findings, the number of the patients with COVID-19, 53 (31.7%) were between the ages of 31 and 35, and at least 36 (21.6%) were between the ages of 17 and 30. Prominent hematology routine outcomes were the number of patients with anemia (103 or 61.7%), neutrophilia (105 or 62.9%), and lymphocytopenia (129 or 77.2%). The D-dimer value increased by 93 (55.7%) patients among 167 COVID-19 patients. Conclusion: Therefore, monitoring the patient's routine hematological presentation and D-dimer level during treatment is essential for preventing mortality and morbidity.